222 THE EFFECTS OF ERYTHROPOIETIN ON CALCIUM SIGNALING IN NEURONAL-LIKE PC12 CELLS. (1st January 2006) - Chan, A.; Peng, H.; Wen, T. C.; Moore, J. E.
Abstract : Background: Erythropoietin (EPO) and EPO receptors are expressed in the central nervous system of mammals. In a number of studies EPO has been demonstrated to be neuroprotective after hypoxic-ischemic insult in vivo and in vitro. The physiology of the EPO-mediated neuroprotective effect, however, is not well understood. Recent indirect evidence has demonstrated that cellular calcium changes are likely involved in the EPO-induced neuroprotection after hypoxic-ischemic insult. The physiological affect that changes in intracellular calcium may play and how calcium regulation is altered by EPO is yet to be determined. Objective: To examine how erythropoietin modulates calcium changes in the neuronal-like PC12 cells in both control and hypoxic conditions in vitro. Methods: Cultures of PC12 cells were obtained from ATCC. Cells were differentiated using nerve growth factor for 3-5 days. EPO receptor expression on the PC12 cells was demonstrated using immunohistochemistry. Cover slips prepared from PC12 cell cultures were preloaded for 30 minutes with Fluo 4 AM. Intracellular calcium changes were studied using fluorescent microscopy, in the presence of EPO 1-100 units/mL in both control cells and after exposure of PC12 cells to 1 hour of hypoxia. EPO was applied to the hypoxic cells 30 minutes, 90 minutes, and 120 minutes after the hypoxic episode. Results: Fluorescent microscopy demonstrated that (1) intracellular free calcium was increased after the application of EPO in control PC12 cells in a dose-dependent manner, (2) after 1 hour of hypoxia the intracellular calcium increase due to EPO reached a level 8 times greater than in PC 12 cells not exposed to hypoxia, and (3) subsequent immunohistochemistry demonstrated an enhanced expression of plasma membrane EPO receptors after PC12 cells were exposed to hypoxic conditions. Conclusion: This study demonstrated that EPO increases intracellular calcium in the neuronal-like PC12 cells in a dose-dependent manner and that the EPO receptor expression and intracellular calcium rise were significantly increased after PC12 cells were exposed to hypoxia. Future Direction: We plan to use pharmacological inhibitors to evaluate whether this rise in cellular calcium is due to calcium coming across the plasma membrane or if calcium is being released from intracellular stores. How alterations in cellular free calcium and the subsequent cellular signals associated with it are involved in the cascade that leads to necrosis, apoptosis, or neuroprotection is going to be crucial in understanding the physiological actions of EPO in the brain.